KEBERTERIMAAN PENGGUNA (MAHASISWA) TERHADAP SISTEM INFORMASI AKADEMIK UNIVERSITAS AIRLANGGA CYBERCAMPUS (UACC) - , Novita Dwi Anawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Reporting mechanism for education and administrative management of the university should be better, effective, and efficient with the academic information system. Airlangga University has been developing the concept of an academic information system comprehensively. Academic information system is known as the University of Airlangga CyberCampus (UACC). Comprehensive academic information system is supposed to work in practice and accepted by users. One of the critical success factors in the implementation of a system is when the system acceptable to the user. This study was conducted to predict the acceptability of user (student) of the UACC using TAM modeling adopted by Davis (1989), Hu, et al. (1999), Davis and Venkatesh (2000). Predictions made by testing the acceptability of the relationship between TAM variables with analysis method of Structural Equation Modeling (SEM). Data retrieved by distributing questionnaires to 220 students (S1 and D3). The study explains that intention to use are not directly affected by perceived usefulness and perceived ease of use through the attitude toward using. Attitude toward using has a strong influence on the intention to use. Based on these findings it can be said that the acceptance by the user (student) of the UACC is positive, it means the students receive for use in academic administration process. Userâs intention (students) to use the UACC under an obligation to use the application for academic administration process.